Women's Resilience in the Work Field in the Novel Lebih Senyap Dari Bisikan by Andina Dwifatma and the Novel Kim Ji-Yeong Born 1982 by Cho Nam-Joo - Regina Antika Regina; Titik Indarti; Resdianto Permata Raharjo (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2025)
Novel Lebih Senyap Dari Bisikan by Andina Dwifatma and novels Kim Ji-Yeong, Born 1982 Cho Nam-Joo's work is similar in its form of female resilience. The two novels will be studied using feminist theory and comparative literature. The focus of the research is how resilient women are in the world of work in the two novels. The aim of this research is to determine the forms of women's resilience in the world of work. The method used in this research is a qualitative descriptive method, data collection techniques using library techniques, data analysis techniques using descriptive techniques, and using time triangulation techniques to test data validity techniques. The research results show that there are similarities and differences in the forms of women's resilience in the world of work. These differences are motivated by life and cultural factors in each novel. Keywords: resilience, feminism, comparative literature